Effect of titanium oxide/reduced graphene (TiO2/rGO) addition onto water flux and reverse salt diffusion thin-film nanocomposite forward osmosis membranes - Amira M. Shawky; Yousra H. Kotp; Mahmoud A. Mousa; Mostafa M. S. Aboelfadl; Eisa E. Hekal; Khaled Zakaria (Environmental Science and Pollution Research, 2024)
Thin-film nanocomposite (TFN) forward osmosis (FO) membranes have attracted significant attention due to their potential for solving global water scarcity problems. In this study, we investigate the impact of titanium oxide (TiO 2 ) and titanium oxide/reduced graphene (TiO 2 /rGO) additions on the performance of TFN-FO membranes, specifically focusing on water flux and reverse salt diffusion. Membranes with varying concentrations of TiO 2 and TiO 2 /rGO were fabricated as interfacial polymerizing M-phenylenediamine (MPD) and benzenetricarbonyl tricholoride (TMC) monomers with TiO 2 and its reduced graphene composites (TiO 2 /rGO). The TMC solution was supplemented with TiO 2 and its reduced graphene composites (TiO 2 /rGO) to enhance FO performance and reverse solute flux. All MPD/TMC polyamide membranes are characterized using various techniques such as scanning electron microscopy (SEM), atomic force microscopy (AFM), and contact angle measurements. The results demonstrate that incorporating TiO 2 /rGO into the membrane thin layer improves water flux and reduces reverse salt diffusion. In contrast to the TFC membrane (10.24 L m −2 h −1 and 6.53 g/m 2 h), higher water flux and higher reverse solute flux were detected in the case of TiO 2 and TiO 2 /rGO-merged TFC skin membranes (18.81 and 24.52 L m −2 h −1 and 2.74 and 2.15 g/m 2 h, respectively). The effects of TiO 2 and TiO 2 /rGO stacking on the skin membrane and the performance of TiO 2 and TiO 2 /rGO skin membranes have been thoroughly studied. Additionally, being investigated is the impact of draw solution concentration. Graphical Abstract